Magnetic resonance evaluation with staging of biopsy proven cases of cancer cervix and to compare with FIGO staging - Parul Dutta; Prabahita Baruah; Aswin Padmanabhan; Karuna Hazarika (Wolters Kluwer Medknow Publications, 2016)
Background: Cervical cancer in India and many other developing countries is a public health concern affecting women of all age groups. The prognosis of cervical cancer is based on the stage, size, and histological grade of the primary tumour and the status of the lymph nodes. Assessment of the stage of disease is important in determining whether the patient may benefit from surgery or will receive radiation therapy. Currently MRI (Magnetic Resonance Imaging) due to its excellent soft-tissue contrast resolution, which exceeds that of CT (Computed Tomography) scanning and ultrasonography, is slowly gaining momentum in pre-treatment evaluation of cancer cervix. Materials and methods: The study was conducted as an analytical study comparing Clinical and MRI staging methods for carcinoma cervix using the same basic staging criteria advised by FIGO (The International Federation of Gynecology and Obstetrics). Total of 48 cases were studied. Results: MRI evaluation of cancer cervix cases with vaginal invasion, parametrial invasion, bowel and bladder invasion etc. were done and compared with histopathological findings. Conclusion: it is recommended that MRI could be included in routine staging of all cases of cancer cervix.